Self‐regulation of the brain's right frontal Beta rhythm using a brain‐computer interface. (2nd June 2022) - Enz, Nadja; Schmidt, Jemima; Nolan, Kate; Mitchell, Matthew; Alvarez Gomez, Sandra; Alkayyali, Miryam; Cambay, Pierce; Gippert, Magdalena; Whelan, Robert; Ruddy, Kathy
Abstract: Neural oscillations, or brain rhythms, fluctuate in a manner reflecting ongoing behavior. Whether these fluctuations are instrumental or epiphenomenal to the behavior remains elusive. Attempts to experimentally manipulate neural oscillations exogenously using noninvasive brain stimulation have shown some promise, but difficulty with tailoring stimulation parameters to individuals has hindered progress in this field. We demonstrate here using electroencephalography (EEG) neurofeedback in a brain‐computer interface that human participants ( n = 44) learned over multiple sessions across a 6‐day period to self‐regulate their Beta rhythm (13–20 Hz), either up or down, over the right inferior frontal cortex. Training to downregulate Beta was more effective than training to upregulate Beta. The modulation was evident only during neurofeedback task performance but did not lead to offline alteration of Beta rhythm characteristics at rest, nor to changes in subsequent cognitive behavior. Likewise, a control group ( n = 38) who underwent training to up or downregulate the Alpha rhythm (8–12 Hz) did not exhibit behavioral changes. Although the right frontal Beta rhythm has been repeatedly implicated as a key component of the brain's inhibitory control system, the present data suggest that its manipulation offline prior to cognitive task performance does not result in behavioral change in healthy individuals. Whether this form of neurofeedback training could serve as a useful therapeutic target for disorders with dysfunctional inhibitory control as their basis remains to be tested in a context where performance is abnormally poor and neural dynamics are different. Abstract : Using a non‐invasive brain‐computer interface, volitional self‐regulation of the right frontal Beta rhythm was achieved in the absence of exogenous brain stimulation. However, this modulation had no impact on behavior in healthy individuals. Whether this form of neurofeedback training could serve as a useful therapeutic target for disorders with dysfunctional inhibitory control as their basis remains to be tested in a context where performance is abnormally poor and neural dynamics are different.